The Effect of Partial Defoliation on Growth Characteristics of Vitis vinifera L. cv. Cabernet Sauvignon I. Vegetative Growth - Hunter, J.J.; Visser, J.H. (South African Journal of Enology and Viticulture, 2017)
The effect of partial defoliation of the whole canopy on vegetative growth of Vitis vinifera L. cv. Cabernet Sauvignon was investigated. Vegetative growth of vines followed the well-known pattern for 0%, 33% and 66% defoliation, i.e. an increase until veraison followed by a decline. Partial defoliation conducted from different developmental stages had no significant effect on leaf area and main shoot length at subsequent developmental stages. The earlier defoliation was applied, the more lateral shoot length and the number of lateral shoots increased, resulting in higher total shoot lengths but no significant differences in cane mass. Partial defoliation from veraison had no effect on lateral growth. Canopy density and relative humidity decreased, while sunlight penetration and windspeed increased in the canopy with partial defoliation. The improved canopy light environment facilitates improved photosynthetic efficiency of leaves as well as development and composition of grapes.